Understanding Consumer Dynamics in East Timor’s Rice Value Chain: A Comprehensive Analysis - Cristóvao Reis; Domingos Soares; Agostinho Coelho; Mateus Pinto; Francisco Assis Lima (Business, Management and Economics: Research Progress Vol. 6, 2024)
The purpose of this work is to identify the links in the rice chain, and to characterize the consumers, along with their segments. Several challenges reduce the value of rice for consumers and the profitability of stakeholders, especially producers, while also limiting the sector’s contribution to the country’s socioeconomic development. The consumer is an important factor in measuring the performance of the rice agri-food value chain in East Timor. The methodologies used to represent the functioning of consumer preferences are cluster analysis, the K-Mean method, qualitative nature, exploratory factor analysis (EFA), and regression analysis. The questionnaire was performed face-to-face, by the researcher. The data collected was analyzed descriptively, using cluster analysis to obtain the consumer segments and factor analysis to obtain the dimensions of value chain analysis. These analyses were performed using the Statistical Package for the Social Sciences (SPSS 24.0) software. A sample of 240 rice consumers from the county of Dili, the capital of Timor-Leste, was selected, and the questionnaire was administered in the presence of the researcher. As consumers become more aware and experience higher purchasing standards, failure to consider their concerns will affect the profit of value chain participants, many of whom will need to update their practices. The result of the KMO statistic, 0.781, shows that the Quality of the analysis is good and the null hypothesis of Bartlett’s test of sphericity was rejected. Two components were identified; the first was found to have a higher weight of characteristics related to availability, transportation, and distance, while the second component had a higher weight of variables linked to Quality, human benefit, and healthy living. Access was the first component and Quality was the second. The study identified four consumer segments and surveyed them considering rice taste, food security, sustainability, and access. These segments can be used by public and private sector organizations as well as individuals to promote the sustainability of the rice value chain in East Timor.